Affective temperament, social support and stressors at work as the predictors of life and job satisfaction among doctors and psychologists - Jaredić Biljana; Hinić Darko; Stanojević Dragana; Zečević Snežana; Ignjatović-Ristić Dragana (Vojnosanitetski Pregled)
Background/Aim. Affective temperament, social support and work-related stresors belong to the group of life and job satisfaction indicators. The aim of this research was to examine predictive roles of the basic affective temperament traits, social support and work-related stressors in the feeling of job and life satisfaction among doctors and psychologists. Methods. The sample consisted of 203 individuals out of whom there were 28% male and 72% female doctors (61%) and psychologists (39%), 25–65 years old (39.08 ± 9.29), from the two university towns in Serbia. The set of questionnaires included Serbian version of the Temperament Evaluation of Memphis, Pisa, Paris and San Diego – autoquestionnaire version (TEMPS-A), Satisfaction with Life scale, Job Satisfaction Survey, short Interpersonal Support Evaluation List, and Source of Stress at Work Scale (IRSa) for estimating the frequency of stressors at work. Results. According to the existing norms our examinees are satisfied with their life, but considerably less satisfied with their work, specially with pay and benefits, while they are most satisfied with nature of work itself and social relations with co-workers and supervisors. Our results show that depressive and hyperthymic, and to some extent cyclothymic temperament traits of the affective temperament significantly predict 21% of life satisfaction variance. Situational factors, such as stressors at work and social support, are important in predicting job satisfaction (58% of variance) with no significant contribution of temperament traits. The analysis did not point out any significant relation of sex, occupation, and age with life and job satisfaction. Conclusions. Affective temperaments can be regarded as predictors of life satisfaction, but in order to better predict satisfaction the aspects of wider social surrounding and sources of stressors at work must be taken in consideration. Future studies should consider other indicators of life satisfaction such as family or health satisfaction, stressors outside of work situations, and negative aspects of caregiving, for example hyperactivation. [Projekat Ministarstva nauke Republike Srbije, br. III 47023: Kosovo and Metohija between national identity and European integration, br. 175014 i br. 175007]